Research on the Upgrading and Development of Ski Industry in Heilongjiang Province under the Opportunity of 2022 Beijing Winter Olympic Games - Bao, Dapeng (Journal of Theory and Practice of Management Science, 2024)
At present, there are two bottlenecks in the development of skiing industry in Heilongjiang Province, that is, the total number of customers has not broken through for a long time, and it is in a downward trend; the number of users of each skiing enterprise is very thin, which can not support the operating expenditure, which shows that the sustainability of the development of skiing industry in Heilongjiang Province is greatly weakened, and how to improve the sustainability of development is a problem worthy of attention of skiing enterprises. At this time, the emergence of the Beijing Winter Olympic Games has given Heilongjiang Province ski industry the direction to break through the bottleneck and improve the development sustainability. Ski enterprises can use the appeal and audience groups of the Beijing Winter Olympic Games to achieve their goals. This paper will analyze this and elaborate the ways and strategies to achieve the goals. Selecting Chinese A-share listed companies from 2011 to 2019 as research samples, this paper empirically tests that the higher the development of the regional digital economy, the lower the synchronization of corporate stock prices. The same conclusion is obtained after the robustness test. The mediation effect test shows that the digital economy reduces stock price synchronization by inhibiting real earnings management. Further research proves that the digital economy has more significant synchronization with enterprise stock prices in non-state-owned enterprises with close attention paid by analysts. The research conclusion has important enlightenment for listed companies, regulatory authorities, and investors.